Vitamina D e prevenzione cardiovascolare - Luca Di Lullo; Rodolfo Rivera; Fulvio Floccari; Vincenzo Barbera; Antonio Bellasi; Antonio De Pascalis; Domenico Russo; Luigi Russo; Francesca Santoboni; Claudio Ronco (AboutScience Srl, 2016)
Abstract non disponibile (Cardionephrology)